Encyclopedia of Analytical Chemistry 2009
DOI: 10.1002/9780470027318.a9038
|View full text |Cite
|
Sign up to set email alerts
|

Amyloids and Protein Aggregation—Analytical Methods

Abstract: More than 30 diseases are associated with amyloid‐forming proteins, which undergo conformational alterations and “misfolding” under particular conditions. These proteins deposit as insoluble proteinaceous aggregates generating disease‐specific histopathologic lesions. The proteins contributing to each disease have dissimilar sequences and native structures, yet they share the commonality of forming insoluble amyloid aggregates characterized by fibrillar morphology and cross‐β structure. Presently, it is though… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(95 citation statements)
references
References 229 publications
5
88
0
Order By: Relevance
“…Amyloid aggregation is accompanied by conformational change in the aggregating protein to β-sheet-rich structure57. To analyze secondary structure, far-UV (190–260 nm) CD spectra were recorded using Jasco 1500 spectropolarimeter and 1 mm path length quartz cuvette.…”
Section: Methodsmentioning
confidence: 99%
“…Amyloid aggregation is accompanied by conformational change in the aggregating protein to β-sheet-rich structure57. To analyze secondary structure, far-UV (190–260 nm) CD spectra were recorded using Jasco 1500 spectropolarimeter and 1 mm path length quartz cuvette.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent contribution, Walter et al blended the pinching capacity of a nanomechanical DNA origami forceps [158] with the biosensing capacity of split aptamer systems [159]. Indeed, the constituting sequences of the ATP-specific split aptamer were equipped with green-and red-emitting photostable cyanine dyes that act as energy donor and acceptor, respectively [160] and were subsequently appended on one arm of the DNA origami forceps.…”
Section: Aptamers As Key Components In the Fabrication Of Smart Dna Omentioning
confidence: 99%
“…Congo Red is used to stain and detect amyloid depositions in tissues. Upon binding to amyloid structures, Congo Red yields a unique blue-green birefringence under a cross-polarized light microscope [159].) Farrar et al [127] concluded that β55 may have bound smaller aggregates, including oligomers, of Aβ peripheral to the dense plaques based on their observation that β55 apparently bound low-molecular-weight oligomers of Aβ40 and Aβ42 on SDS-PAGE gels, and similar observation reported by Koffie et al [163], showing a "halo of oligomers" surrounding the plaques detected by a so-called "conformation-specific" NAB61 antibody [164].…”
Section: Aptamers and Aβmentioning
confidence: 99%
See 1 more Smart Citation
“…Xray studies could provide a high-resolution structure, but for protein aggregates it is typically difficult to obtain a crystal with high diffraction quality needed for X-ray studies [129].…”
Section: Introductionmentioning
confidence: 99%